KREATIFITAS DAN INOVASI DALAM PENDIDIKAN - Elizabeth Hateyong; Siti Irene Astuti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
Technological developments and global challenges in the digital era require education to provide creative and innovative learning. Creativity is understood as the ability to generate original and useful ideas, while innovation is the application of these ideas to create added value. This study discusses the concepts of creativity and innovation in education, the role of teachers and educational institutions in developing them, and the obstacles faced in their implementation. Various challenges, such as limited facilities, a rigid curriculum, minimal teacher competency, and an unsupportive school culture, are identified as key inhibiting factors. This study also proposes strategies for developing creativity and innovation at the school, teacher, government, and student levels. Synergy between all stakeholders is key to creating an adaptive, relevant education ecosystem that is able to meet the needs of the 21st century. Thus, the development of creativity and innovation is a crucial element in the transformation of education towards dynamic and sustainable learning.